Synteny in Toxigenic Fusarium Species: The Fumonisin Gene Cluster and the Mating Type Region as Examples - Waalwijk, C.; van der Lee, T.; de Vries, I.; Hesselink, T.; Arts, J.; Kema, G.H.J.
A comparative genomic approach was used to study the mating type locus and the gene cluster involved in toxin production (fumonisin)in Fusarium proliferatum, a pathogen with a wide host range and a complex toxin profile. A BAC library, generated from F. proliferatum isolate ITEM 2287, was used to identify chromosomal regions flanking the mating type locus and the gene cluster involved in the biosynthesis of fumonisin. These regions were sequenced and compared with corresponding sequences in other ascomycetes. The results demonstrated that the level of synteny between ascomycetes can vary greatly for different genomic regions and that the level of similarity of genes within a region can also fluctuate strongly. Synteny was found in the regions flanking the mating type idiomorph among ascomycetes that supposedly diverged 280 million years ago. The fumonisin gene clusters of F. proliferatum and F. verticillioides were completely syntenic but absent in F. graminearum. The regions flanking the fumonisin gene clusters were highly dissimilar between F. proliferatum and F. verticillioides, whereas they formed a continuous region in F. graminearum. This indicates that the fumonisin gene cluster has been inserted at different genome locations in both species. Surprisingly low similarity was found between the corresponding genes within the fumonisin cluster of F. proliferatum and F. verticillioides, compared to other genomic sequences indicative for two independent acquisition events from distinct genetic sources. The results demonstrate the power of comparative genomics for gene annotation and for studies on the evolution of genes, gene-clusters and species.
Keywords: GENOME; GIBBERELLA; PLANT PATHOGEN; TOXIN